EVIDENCE BASED PRACTICES IN EARLY INTERVENTION (Annual of the Faculty of Philosophy in Skopje, 2019)
The Government of Republic of North Macedonia has made a commitment tocare and education for children with developmental delays by signing the Conventionon the Rights of the Child. Nevertheless, early intervention centres in NorthMacedonia cannot always meet the preconditions and ease access and care for childrenwith developmental disabilities or delays. In the U.S. services for young children,from birth to the 3rd birthday are called Early Intervention (EI) or Part C services.Once the child turns three (and until 21), educational services are providedunder Part B of IDEA. EI focuses on family-centred services, individually plannededucational programs, and specialized teaching approaches.The primary aim of the research was to explore the EI system in the States aswell as the implementation of policy into practice. The secondary goal was related toidentifying positive practices and policies that can be applied in an internationalcontext. A qualitative study research methodology was used with a non-rigid andnaturalistic design. Qualitative content analysis was the research tool. This papercontains a qualitative review of papers in the following areas: Historical trends inEI; Current trends in EI; Models of service delivery; Transdisciplinary EI approach;and Coaching of families within EI.
Keywords: EARLY INTERVENTION; TRANSDISCIPLINARY APPROACH; DISABILITY POLICIES; QUALITATIVE METHODOLOGY